Social Media- A Renewed Approach to Green Tourism by Millennials (Trinity Journal of Management, IT & Media (TJMITM), 2023)
This paper explores the utilization and significance of social media in advancing  eco- friendly tourism among the Millennial demographic amidst the challenges  posed by the global COVID-19 pandemic. Reviving green tourism during this  period presents a notable challenge for the industry, prompting the implementation  of various marketing strategies aimed at engaging Millennials in sustainable  travel practices. Social media emerges as a pivotal tool in raising awareness and  fostering green tourism among Millennials, demonstrating its effectiveness in  driving positive outcomes for sustainable tourism initiatives. Thus, this paper  offers insights into the crucial role played by social media in promoting eco friendly tourism among Millennials and facilitating informed decision-making  for sustainable travel experiences.
Keywords: Green Tourism; Millennial; Social Media; Sustainability; Nature